An explorative study of knowledge transfer processes in new product development in the automotive industry - Engel, Rupert (Cranfield University, 2004)
This research builds on three projects that aim to investigate how knowledge transfer takes place in new product development in the automotive industry. The study seeks to picture how product development teams frame and shape new product knowledge, how they interpret such knowledge, and how they apply knowledge to the product development process. From that perspective, product development activities can be seen as transactions that are integrated into an overall system of identifying, assessing, collecting and combining knowledge. Results of my research so far reveal that there are many factors that affect the successful management of knowledge transfer in new product development projects. Based on my first two projects, using the case study approach, it is evident that for successful knowledge transfer to occur, there is a need to distinguish between design knowledge that is embedded in the tacit knowledge domain and that embedded in the or explicit design knowledge domain. The results of project three, using a survey questionnaire approach, provide a powerful demonstration, that knowledge integration, combination and creation in product development need intensive interaction and collaboration. The enormous importance of interaction and collaboration to integrate and combine knowledge has its origin in the nature of design knowledge. For example engineers produced in the survey a 82 % rate of agreement with the statement that they use mainly knowledge that comes from their past work experience as product developers, in order to solve complex design tasks. The underlying assumption of this finding is, that engineers are therefore mostly forced to transfer tacit design knowledge to solve complex design tasks. The research showed that a remarkable under-performance exists in knowledge identification and knowledge articulation in new product development in the automotive industry. In vehicle development, non-routine tasks are highly complex. This requires team members to have an understanding of the complete product system architecture. To create such an understanding, engineers need to identify and articulate knowledge. These activities can be seen as a pre-knowledge creation. The result is a shared product knowledge base, which makes it possible for people engaged in the vehicle development process to use different kinds of knowledge to capture and link new technologies into innovative products. This may require a cultural shift by vehicle manufacturers in terms of how they steer and allocate resources to future vehicle development programmes. Building on four years engagement with knowledge transfer research, I conclude that organisations in the automotive sector still rely on methods and processes that were successful in the past and strictly directed at exploiting tangible assets. To integrate preknowledge creation, as a new found discipline in product development projects creates an enormous potential to integrate and combine knowledge in an efficient way for future product development projects.
Keywords: Vehicle development; Product development